New Digital Tools for a New Critical Edition of the Hebrew Bible - Yardney, Sarah (Open theology, 2019)
This article describes the digital edition of the Hebrew Bible: A Critical Edition (HBCE), which is being produced as part of a project called Critical Editions for Digital Analysis and Research (CEDAR) at the University of Chicago. We first discuss the goals of the HBCE and its requirements for a digital edition. We then turn to the CEDAR project and the advances it offers, both theoretical and technological. Finally, we present an illustration of how a reader might use the digital HBCE to interact with the biblical text in innovative ways.